Use of combined method, accelerometer and international physical activity questionnaire, to determinate occurence of physical inactivity in adults - Rodrigo Pereira da Silva; Evandro Forneas Sperandio; Agatha Caveda Matheus; Vinicius Tonon Lauria; Flavio Rossi de Almeida; Vitor Rossi de Almeida; Antonio Ricardo Gagliardi; Rodolfo Leite Arantes; Marcelo Romiti; Victor Zuniga Dourado (Motriz: Revista de Educacao Fisica, 2017)
Abstract Aim Evaluate and compare the proportion of PI and associated factors by IPAQ questionnaire, triaxial accelerometry and the combination of both. Adults aged ( 18 years were enrolled (n = 250). Methods We considered PI as < 600 MET-min/wk in the IPAQ total score, < 150 min/wk of moderate-to-vigorous physical activity in 7 days accelerometry, and the combination of both criteria. Clinical assessment, spirometry, cardiopulmonary exercise test, bioelectrical impedance, isokinetic dynamometry, postural balance, and six-minute walk test were also performed. For participants practicing aquatic, martial arts or cycling, only the IPAQ criterion was considered. Results Proportions of PI were significantly different among methods (IPAQ, 10%; accelerometry, 20%; combination, 25%). After multivariate logistic regressions, PI was determined by age, sex, educational level, risk factors for cardiovascular disease, lean body mass, cardiorespiratory fitness, and postural balance. Conclusion Thus, the combined method for determining PI and associated factors in adults showed great validity, indicating that questionnaires and accelerometers are complementary and should be utilized in combination in epidemiological studies.